Prevalence of Cardiovascular Risk Factors Among Health Care Professionals of Rawalpindi & Islamabad - Muhammad Ehab Azim, Malik Muhammad All A wan, Waleed Rafiq, Furqan Ahmed Siddiqi Naureen Tassadaq, Fozia Sibtain, Muhamamd Furgan Yagool), Aamir Raoof Memon , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To find the prevalence of different cardiovascular risk factors among different health care professionals in Rawalpindi and Islamabad. Study design: Cross sectional survey Place and Duration: Hospitals ofRawalpindi and Islamabad, from January 2014 to June 2014. Subjects and Methods: This study was a conducted on 200 health care professionals using convenient sampling technique. We included in the study, health care professionals aged 24-65 years belonging to Rawalpindi and Islamabad. A questionnaire was developed containing 23 questions out of which 21 were close ended and 2 were open ended with a modification in some of the questions also. International Physical Activity Questionnaire (IPAQ) was added because of its high reliability and validity. Results: Majority of participants in this study (70.1%) had a normal body mass index 18.6-24.9 kg7m) whereas only 12.1% were overweight and 5.6% were obese. Underweight participants contributed to 12.1% of the study population. There were 41.1% HCPs having low level of physical activity, It was found that 52.3% health care professionals had family history of cardiovascular risk factors. Moreover 50% health care professionals in this study had first degree relatives having cardiovascular diseases. Conclusion: Being the health care professionals. majority of the respondents have awareness about risk factors for cardiovascular diseases yet a major portion of them was found to have at least one contributing factor for cardiovascular diseases. The most likely risk factors were poor dietary habits followed by positive family history and low levels of physical activity.